Measuring Impact of the Accrual Accounting Implementation on Fiscal Transparency Quality: A Mixed Methods Study in Indonesia - Donny Maha Putra; Wiwit Apit Sulistyowati (Journal of Accounting and Investment, 2021)
Research aims: This study aims to measure the correlation between the Indonesian government accounting system's accrual basis and fiscal transparency quality. Furthermore, this study deepens the research results through focus group discussion (FGD) at Line Ministries.Design/Methodology/Approach: This study used a mixed methods, in which the quantitative approach employed a questionnaire instrument, while the qualitative approach utilized interviews and FGD. This study involved 149 respondents at the accounting unit based on the purposive sampling technique, using questionnaire instruments and interviews with 77 users. Also, this study utilized Structural Equation Modelling (SEM), and the data were then processed through LISREL 8.8 statistical software.Research findings: This study proved that accruals' implementation had a significant positive impact on the quality of government fiscal transparency. The FGD results revealed that accrual accounting practices still referred to the government accounting standards. Meanwhile, the quality of fiscal transparency had been reviewed in advance by the auditor team, and the auditor's recommendations were taken into consideration in determining strategic decisions by estimating the potential risks that would arise.Theoretical contribution/Originality: This study contributes to an extended approach by examining the effect of the accrual accounting application’s effectiveness on the quality of government fiscal transparency. In addition, this study strengthens previous studies by using qualitative approaches through FGD involving units related to institutions and ministries. Therefore, this study’s results provide empirical evidence, which is theoretically very limited.Practitioner/Policy implication: This study contributes as an academic reference to improvements in developing a policy model for the accrual implementation in the government accounting system, especially in Indonesia.Research limitation/Implication: Respondent data for interviews is still limited to the managerial level. Therefore, to obtain more in-depth results, the subsequent study can be conducted at the operational level.